Temperature- and pH-responsive injectable chitosan hydrogels loaded with doxorubicin and curcumin as long-lasting release platforms for the treatment of solid tumors - Li, Na; Lin, Jianjun; Liu, Chunping; Zhang, Qian; Li, Riwang; Wang, Chuang; Zhao, Chaochao; Lu, Lu; Zhou, Changren; Tian, Jinhuan; Ding, Shan (Frontiers in Bioengineering and Biotechnology, 2022)
The efficacy of treating solid tumors with chemotherapy is primarily hindered by dose-limiting toxicity due to off-target effects and the heterogeneous drug distribution caused by the dense extracellular matrix. The enhanced permeability and retention (EPR) effect within tumors restricts the circulation and diffusion of drugs. To overcome these obstacles, hydrogels formed in situ at the tumor site have been proposed to promote drug accumulation, retention, and long-lasting release. We developed a thiolated chitosan (CSSH) hydrogel with a gelation point of 37°C. Due to the pH-sensitive characteristics of disulfides, the prepared hydrogel facilitated drug release in the acidic tumor environment. A drug release system composed of hydrophilic doxorubicin (Dox) and hydrophobic liposome-encapsulated curcumin (Cur–Lip) was designed to enhance the long-lasting therapeutic impacts and reduce adverse side effects. These composite gels possess a suitable gelation time of approximately 8–12 min under physiological conditions. The cumulative release ratio was higher at pH = 5.5 than at pH = 7.4 over the first 24 h, during which approximately 10% of the Dox was released, and Cur was released slowly over the following 24–120 h. Cell assays indicated that the Cur–Lip/Dox/CSSH gels effectively inhibited the growth of cancer cells. These in situ-formed Cur–Lip/Dox gels with long-term drug release capabilities have potential applications for tumor suppression and tissue regeneration after surgical tumor resection.